Development dynamics of health and social infrastructure for the long-term care - The case of the Posavje region - Bogataj David; Bogataj Marija; Kavšek Marta (Sciendo, 2021)
The populations of rural areas across Europe, especially Slovenia, are ageing rapidly and the areas themselves are becoming depopulated. Therefore, this study aims to contribute to our understanding of the population dynamics and provide a method for forecasting housing and other long-term care needs.